Ephedrine versus Phenylephrine: Prevention of Hypotension during Spinal Anaesthesia for Cesarean Section and Effects on the Fetus (Journal of the Bangladesh Society of Anaesthesiologists, 2017)
Background: Hypotension during spinal anaesthesia for cesarean section is secondary to the sympathetic blockade and aorto-caval compression by the uterus and it can be deleterious to both the fetus and the mother. Ephedrine and phenylephrine improve venous return after sympathetic blockade during the spinal anaesthesia.Aim: The aim of this study was to compare intravenous bolus doses of phenylephrine and ephedrine in preventing and treating hypotension in spinal anaesthesia for caesarean section and the effect of vasopressors on fetal outcome in terms of Apgar score.Materials and Methods: Total 100 patients of ASA Grade I undergoing caesarean section under spinal anaesthesia with a normal singleton pregnancy beyond 37 weeks gestation was randomly allocated into two groups of 50 each. Group I received prophylactic bolus dose of ephedrine 10 mg IV at the time of intrathecal block with rescue boluses of 5 mg. Group II received prophylactic bolus dose of phenylephrine 100 ¼g IV at the time of intrathecal block with rescue boluses of 50 ¼g. Hemodynamic variables like blood pressure and heart rate was recorded every 2 minutes up to delivery of baby and then after every 5 minutes. Neonatal outcome was assessed using Apgar score at 1 and 5 minutes and neonatal umbilical cord blood pH Values.Results: There was no difference found in managing hypotension between two groups. Incidence of bradycardia was higher in phenylephrine group. The differences in umbilical cord pH, Apgar score, and birth weight between two groups were found statistically insignificant.Conclusion: Ephedrine and Phenylephrine are equally efficient in managing hypotension during spinal anesthesia for caesarean section. There was no difference between two vasopressors in the incidence of true fetal acidosis. Neonatal outcome remains equally good in both the groups.JBSA 2017; 30(1): 41-47